1984
DOI: 10.1037/0021-9010.69.4.574
|View full text |Cite
|
Sign up to set email alerts
|

Inflation bias in self-assessment examinations: Implications for valid employee selection.

Abstract: Self-assessment examinations were administered to job applicants for 13 different occupational classes These examinations were composed of lists of tasks that were either job-related as determined by a job analysis or bogus but superficially resembling the job-related tasks Applicants were asked to rate the extent of their training and experience on each task Analysis of these ratings revealed that inflation bias was prevalent and pervasive. A subsequent test of five clerical classes demonstrated that inflatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 19 publications
2
84
0
Order By: Relevance
“…Walfish et al's (2012) findings, it is evident that psychological therapists overestimate both their individual skill level and their therapy Self-assessment bias 14 outcomes relative to their peers. This self-assessment bias is not unique to therapists, but occurs in many domains of human activity (e.g., Anderson et al, 1984). A potential cause of such a bias is the need to maintain a positive self-image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walfish et al's (2012) findings, it is evident that psychological therapists overestimate both their individual skill level and their therapy Self-assessment bias 14 outcomes relative to their peers. This self-assessment bias is not unique to therapists, but occurs in many domains of human activity (e.g., Anderson et al, 1984). A potential cause of such a bias is the need to maintain a positive self-image.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, no clinicians saw their skill level as being below the 50 th centile, meaning that no-one saw themselves as being below the average level of skill. This overestimation of ability is found in a range of skills, such as driving and job performance (e.g., Anderson, Warner, & Spencer, 1984;Meyer, 1990), and is known as 'self-assessment bias'. Furthermore, when asking these clinicians about how many of their patients recovered or improved, Walfish et al (2012) found that clinicians believe that most of their clients recover after therapy.…”
Section: Disordersmentioning
confidence: 99%
“…Also related is an early study by Anderson, Warner, and Spencer (1984), where a comparable method was used to measure occupation-specific knowledge among job applicants. It is unfor-tunate that this work has not been exploited in the measurement of tacit intelligence (Sternberg, Wagner, & Okagaki, 1993).…”
Section: Applicationsmentioning
confidence: 99%
“…Research has shown incumbents and applicants respond differently when answering preemployment questionnaires (Anderson, Warner, & Spencer, 1984). Although Dweck et al (1995) demonstrated that conception of ability was not related to social desirability, those results…”
Section: Limitations Of the Current Studymentioning
confidence: 50%